Design and Analysis of a Pre-Engineered Warehouse Building Considering Lateral Load Using Etabs - Anuj Kumar; Afzal Khan; Vikas Patidar (International Journal of Scientific Research in Civil Engineering, 2021)
Pre Engineered Building (PEB) is a concept of performing optimization ofstructures providing economical design. Steel is a tensile material whichprovide more strength and available in sections as per requirements. Thesesections are utilize in pre-engineering building. As per Indian standard I.S8020:2007 code is prescribed for designing of steel structures. Based onlimit state design. P.E.B. structures are high in demand as compared toconventional structure i.e Conventional Steel Building (CSB). CSB designconcept is comparatively more easy in fabrication and provide easyrestoration. Steel structures are generally utilized in long span structuressuch as industrial buildings where gantry cranes are installed. Steelstructures are easy to assemble in any place as compared to RCC structurewhere cost and time both are high in comparison. PEB building structure isin demand as it requires less time and provide proper strength.Industrial structures also associate high dead load as it provides residenceto heavy sized members. Therefore, this is necessary to investigate seismicresponse of buildings with various bracings and dampers to controlvibration, lateral displacement and storey drift. Natural time period,frequency, roof displacements are the major parameters considered forobserving response of structures. Response spectrum analysis of 3Dindustrial structure with distinct concentric bracings and dampers usingSAP 2000 will be carrying in this research under respective base shear . In this study we are comparing different segments of building structurewhere analysis is performed considering lateral loading condition.
Keywords: Steel Structure; Conventional Steel Building (CSB); Pre Engineered Building (PEB); Bracing Systems; Wind Analysis; Cross Bracing; Diagonal Bracing; K-Bracing